(untitled) (PERcursos Linguísticos, 2021)
The objective of this article consists to show how it is built the social representation (SR) of a custodian who has a sentence for legal order. The specifically form, we propose to analyze the testimony to verify how the arrested represents himself, the society and the education in the prison system. From the discursive by this social actor, we believe that can understand the construction of the social representation, furthermore this we can reflect about his mental models and generic representations that, although there are in the voice of an individual, they point the group that he is part. For this, we use the theorical parameters based in sociocognitive approach of the Critical Discourse Analysis (CDA) by Van Dijk, as well as the methodological aspects of this theory. The result of the discursive analysis demonstrated that school ambience can allow the custodian a new perspective of life, this includes: jobs, family and social life; despite of the conscience of segregations and prejudice of society.